2014
DOI: 10.1007/s00213-014-3777-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleus accumbens shell infusions of ganaxolone or gaboxadol on ethanol consumption in mice

Abstract: Rationale Allopregnanolone (ALLO) is an endogenous neuroactive steroid thought to alter the reinforcement value of alcohol (ethanol) due to its actions as a positive modulator of the GABAA receptor (GABAAR). Extrasynaptic GABAARs may be a particularly sensitive target of ethanol and neuroactive steroids. Previous work showed that systemic injections of an ALLO analog, ganaxolone (GAN), or an extrasynaptic GABAAR agonist (gaboxadol; THIP), decreased ethanol intake in male mice with limited access to ethanol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
“…A growing number of reports support inhibition mediated by extrasynaptic GABA A receptors as a target for the effects of binge alcohol intoxication and consumption (Nie et al, 2011; Ramaker et al, 2011, 2012, 2014a, 2014b; Fritz and Boehm, 2014). Unlike the classic synaptic subtype of GABA A receptors that mediate phasic inhibition following vesicular release of GABA, extrasynaptic GABA A receptors mediate a constant tonic inhibition, responding to the low to moderate concentrations of ambient GABA found in the extrasynaptic space (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus a potential period of `indecisiveness' on initial lever selection may have contributed to response latency measure not reaching full significance. While these measures have been most highly validated in operant paradigms utilizing higher lever press requirements [1720, 35, 36], the latency to first lick has been validated as a measure of ethanol seeking behavior even in non-operant forms of ethanol self-administration [18, 37]. A similar latency is further used in the study of dopamine regulation of non-operant behavior [5961].…”
Section: Discussionmentioning
confidence: 99%
“…However, the 2-bottle choice paradigm also appears to be sensitive to limited-access procedures. If offered a choice between 10% or 20% (v/v) ethanol and water, B6 mice have been shown to consume ∼2-6.5 g/kg of ethanol and reach BECs ∼50-90 mg/dl in a 2-4 hr period as well as demonstrate an ethanol preference of ∼60-80% (Cozzoli et al, 2014c; Ramaker et al, 2014; Rhodes et al, 2007). Thus, although concurrent access to water does appear to reduce ethanol intake in a limited access paradigm to some degree relative to the standard DID paradigm described above, BECs at the ‘binge’ level (≥ 80 mg/dl) can still be observed.…”
Section: Rodent Models Of Voluntary Binge-like Ethanol Consumptionmentioning
confidence: 99%
“…This is particularly interesting in regard to the aforementioned hypothesis that a pharmacological component of ethanol reward/reinforcement may be GABAergic disinhibition of VTA DA neurons. A prominent projection target of the VTA, the nucleus accumbens shell also regulates 2-bottle DID ethanol intake though GABA A processes as local infusion of the GABA A receptor partial agonist THIP significantly reduced ethanol consumption (Ramaker et al, 2014). Finally, THIP infused into the infralimbic cortex, a region associated with behavioral flexibility and fear extinction (Morgan and LeDoux, 1995; Ragozzino et al, 1999), has been shown to promote ethanol intake in DID and associated BECs (Fritz and Boehm II, 2014).…”
Section: Mechanisms Of Binge-like Alcohol Consumptionmentioning
confidence: 99%